2006
DOI: 10.1093/chemse/bjl039
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Communication Through Chemical Signals in Female Mice: Reinforcing Properties of Involatile Male Sexual Pheromones

Abstract: In rodents, social and reproductive behaviors critically depend on chemical signals, including sexual pheromones that have been suggested (but not demonstrated) to be rewarding. In this work, we analyze this issue by studying the chemoinvestigatory behavior of adult female mice (without experience with male-derived chemicals) toward 1) the synthetic odorant citralva, 2) bedding soiled by different conspecifics (females, males, and castrated males), and 3) volatiles derived from bedding soiled by males and cast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 44 publications
3
60
3
Order By: Relevance
“…Adult females prefer male-to female-derived chemosignals whether presented as an entire anaesthetised animal, a drop of urine or soiled-bedding. Similarly, adult females also prefer intact to castrated male-derived odours (Martinez-Ricos et al, 2007;DiBenedictis et al, 2012).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Adult females prefer male-to female-derived chemosignals whether presented as an entire anaesthetised animal, a drop of urine or soiled-bedding. Similarly, adult females also prefer intact to castrated male-derived odours (Martinez-Ricos et al, 2007;DiBenedictis et al, 2012).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…We hypothesized that the saliency attributed to these odors arises from pheromone-induced activation of the mesolimbic dopamine ‘reward’ system, yet little is known about the neural pathways via which pheromonal stimuli access the mesolimbic dopamine system. Male and female mice will form a conditioned place preference for opposite-sex urinary odors [9,10], suggesting that these odors are rewarding. Additionally, immediate early gene studies have shown that opposite-sex (but not same-sex) conspecific body odorants activate several segments of the brain’s reward circuitry including the mOT (unpublished observations), AcbC, AcbSh, and the ventral tegmental area (VTA) [8,1112].…”
mentioning
confidence: 99%
“…A complementary, non-overlapping function has been suggested for volatile molecules and urinary proteins, as the former may act as olfactory flags for the presence of MUP (MucignatCaretta and Caretta, 1999a), while non-volatile chemosignals may act as natural reinforcers that induce conditioned place preference (Martínez-Ricós et al, 2007). In the majority of cases, the two different components of mice chemosignals, volatile, and non-volatile, have been studied independently, so the contribution of each component in the initial phase of attention orienting to the chemical stimuli remains unclear.…”
Section: Introductionmentioning
confidence: 99%